Unit Roots and Cycles in the Main Macroeconomic Variables for Argentina - Carrera, Jorge Eduardo (1999)
In this paper we study the integration properties of some of the main macroeconomic series of Argentina. We present a robust methodology for the analysis of persistence of shocks affecting macroeconomic series and its consequences on the modeling of the cyclical and permanent components. Our strategy consists on testing the stationarity of the series by using a sequence of indicators in such a way that we can analyze the problem from three converging points of view: Persistence of the series, Unit Root (UR) and UR with a Structural Breaks. In such a way we reach robust results regarding the integration properties of the main 14 Argentinean macroeconomic time series. Thus, we are able to classify them in four homogenous groups according to its order of integration. This allows us to determine the best strategy for modeling the cyclical component of each variable. For example, we found that the GDP can be robustly considered integrated of order one, I(1). Shocks seem to have permanent effects on the GDP and consequently a stochastic process is the best alternative for modeling its behavior. Finally, with respect to the date of the structural break relevant for the Argentinean economy, the years 1988-89 concentrate the greatest number of breaks detected endogenously for the series of these work. Thus, we can conclude that the convertibility does not appear to be a point of structural change in the data generating process of the main macroeconomic series of Argentina.